THE EFFECT OF KNOWLEDGE MANAGEMENT ON THE PERFORMANCE OF INNOVATION DIMEDIATED ORGANIZATIONS IN GOVERNMENT RESEARCH ORGANIZATIONS - Navik Puryantini; Rofikotul Arfati; Bambang Tjahjadi (Universitas Airlangga, 2017)
Inovasi merupakan kekuatan penting dalam peningkatan kinerja organisasi serta dapat meningkatkan pertumbuhan ekonomi dan pembangunan (Agbim, 2013). This study aims to determine the effect of innovation as a mediating variable on the relationship of knowledge management to organizational performance.This study uses a population of employees of government research organizations. Samples were taken by clustering. The data analysis method used in this research is Partial Least Squares. The results showed that there was a direct positive effect on knowledge management innovation and organizational performance. The innovation variable did not succeed in playing a role in the relationship of knowledge management to organizational performance.